Making music in the radio theater when creating a spatial sound picture - Vasilev, Dimitar (Young Scientific Music and Dance Forum : Conference with international participation, 2020)
When creating a spatial sound picture in the radiotheater, the music is also fully involved. It can be composed especially for the production or it may be present as a musical arrangement from excerpts or entire musical works. With the help of the music, the artistic and aesthetic radio dramatic built and certain dramatic moments are reinforced.